Decision-Making System for Determining Tuition Fees using the Simple Additive Weighting Method - Gagah Dwiki Putra Aryono; Kenedi, Kenedi (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
This study aims to develop a decision-making system for determining tuition fees using the Simple Additive Weighting (SAW) method. The SAW method is a multi-criteria decision-making technique that calculates the weighted sum of decision alternative attributes. This system is designed to assist school administration in making decisions related to the determination of tuition fees for students, which is a crucial source of funding for school operations. The system was developed using PHP programming language and MySQL database. This study utilized descriptive research methods and data collection techniques such as interviews, observations, and documentation. The collected data were then analyzed using the SAW method to determine the weight of each attribute and rank the decision alternatives. The system's performance was evaluated using black-box testing methods, and the results indicated that the system exhibited excellent accuracy, reliability, and efficiency. The testing results showed that the developed system can assist school administration in making decisions related to the determination of tuition fees for students. The use of this system can simplify the decision-making process and reduce errors in decision-making, thereby enhancing school operational activities